Competition or cooperation? Jewish day schools, synagogues and the (re)construction of young people's Jewish identities in England. Issue 3 (4th May 2018) - Samson, Maxim G. M.
ABSTRACT: Diasporic synagogues have historically provided a number of educational and social functions. However, the growing popularity of state-funded Jewish schools in England necessitates analysis of these institutions' changing roles and their implications for performances of Jewishness. Drawing upon interviews with rabbis, and interviews and focus groups with parents and students at a Jewish school, this article demonstrates three challenges for synagogues associated with the recent growth in Jewish day schooling: the instigation of instrumental attendance at services in order to secure a school place; and the co-option of synagogues' traditional functions as both education and social centres. In the process, it illustrates how conceptualisations of Jewish identity are contested, resulting in discrepant attitudes towards Jewish education. Consequently, the article contributes to understandings of the spaces in which young people practise their Jewishness, and highlights the challenges for community leaders in ensuring that Jewish schools and synagogues cooperate rather than compete.